1998
DOI: 10.1073/pnas.95.25.15145
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of prehistoric human mobility in Polynesia indicated by mtDNA from the Pacific rat

Abstract: Human settlement of Polynesia was a major event in world prehistory. Despite the vastness of the distances covered, research suggests that prehistoric Polynesian populations maintained spheres of continuing interaction for at least some period of time in some regions. A low level of genetic variation in ancestral Polynesian populations, genetic admixture (both prehistoric and post-European contact), and severe population crashes resulting from introduction of European diseases make it difficult to trace prehis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
86
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 19 publications
5
86
2
1
Order By: Relevance
“…Fresh tissues were extracted as described (9). We amplified and sequenced Ϸ240 base pairs of the hypervariable mitochondrial control region; see Supporting Text, which is published as supporting information on the PNAS web site, for specific methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh tissues were extracted as described (9). We amplified and sequenced Ϸ240 base pairs of the hypervariable mitochondrial control region; see Supporting Text, which is published as supporting information on the PNAS web site, for specific methods.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research focused on mtDNA variation within East Polynesian populations of R. exulans (9) and showed that this rat was an excellent proxy for tracing the movement of prehistoric Polynesian peoples. Our analyses identified interaction spheres and specific population origins within Polynesia.…”
mentioning
confidence: 99%
“…This process of cultural assimilation and absorption has likely characterized much of coastal Southeast Asia (9), obscuring the previously more widespread distribution of human mtDNA Haplogroup B that may have existed 3,500 years ago. Thus, the analyses of pig and wild boar diversity may provide information not available from examining only human variation as has been shown for analyses of the Pacific rat (14)(15)(16). Additional sampling of Southeast Asian wild boar diversity is required to further refine the site of domestication of the PC of pigs and potentially the proximate origin of the Lapita cultural complex (Fig.…”
Section: Origin Of the Pc And Implications For Human Settlement Of Thmentioning
confidence: 99%
“…On smaller islands of Micronesia and Polynesia in particular the pig disappeared from the archaeological record before European contact, presumably because of its adverse competition with humans for land resources (12,13). The Pacific rat, Rattus exulans, is thus the most widespread of the introduced animals of the Pacific and as such has been used effectively as a proxy for human settlement and exchange (14)(15)(16). Unlike the European introduced rats of distinct species that could not interbreed with the Pacific rat, studies of Pacific pigs, dogs, and chickens are complicated by the introduction of conspecifics within the last few hundred years.…”
mentioning
confidence: 99%
“…Alternative approaches have focused on commensals and parasites that accompany human migrations, including viruses such as JC virus (20,21) and human T-lymphotrophic virus (22), fungi (23), rats (24), and the bacterium Helicobacter pylori (25)(26)(27). In the present study, we investigated the usefulness of H. pylori, a Gram-negative bacterium that persistently colonizes the stomach of Ͼ50% of humans, as a potential genetic marker for deciphering recent human migrations.…”
mentioning
confidence: 99%